Income Optimization Model for Traditional Woven Craftsmen - Neneng Miskiyah; Yulia Pebrianti; Purwati; Keti Purnamasari (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to analyze and optimize the household income of Palembang woven fabric craftsmen. It employs an optimal response surface regression model to identify the ideal levels of working capital, business experience, partnerships, and working hours that maximize household income. To establish the relationship between the tar-get response and the independent variables, the study uses a second-order central composite design within a quadratic model framework. The research sample consists of craftsmen who are members of the Griya Tuan Kentang joint business group, with data collected through questionnaires. The findings indicate that the optimal working capital is IDR 12,069,541.74. This amount enables craftsmen to manage periods of declining demand and rising raw material costs while minimizing unnecessary ex-penses and increasing profitability. The study also reveals that 18.2 years of business experience is the optimal duration for achieving superior business performance. This level of experience allows craftsmen to set realistic, long-term business goals. Fur-thermore, an optimal working schedule of 7.99 hours per day ensures efficient produc-tivity without compromising work quality or work–life balance. Finally, maintaining a partnership for two years is identified as the ideal duration. This period encourages craftsmen to regularly evaluate and enhance the sustainability of their partnerships, effectively optimizing resources and networks.